Er:YAG and Nd:YAG laser irradiation effect on dental root cut: A SEM analysis - Mello, Guilherme Paulo S.; Paradella, Thaís Cachuté; Munin, Egberto; Mello, José Benedicto; Pacheco, Marcos Tadeu T.; De Toledo Porto Neto, Sizenando [UNESP] (SPIE, the international society for optics and photonics, 2000)
The root end cut, also called apicoectomy, consists on the surgical removal of the root's end, as one of the last alternatives for teeth preservation. This procedure may be done with conventional diamond burs, as well as Er:YAG laser only, or in association with Nd:YAG laser. In this paper, the quality of the root end cut for the different mentioned procedures, was compared for a better analysis of these techniques, regarding surface finishing. The Er:YAG laser dosimetry applied during the experiment was of 400 mJ/10 Hz, using a laser beam with a 0.8 mm diameter. The Nd:YAG laser was irradiated at 1.5 W/10 Hz, being the samples submitted to a scanning electron microscope. On the Er:YAG laser irradiated samples, there was absence of smear layer, as well as the presence of some open dentinal tubules, presenting the surface a smooth texture. On the roots cut with the Er:YAG laser, in association with the Nd:YAG laser, below the ablative regime, there was the presence of a melted dentin surface, with an appearance which suggests a non-crystalline structure, closing the tubules. Regarding the conventional apicoectomy, the samples presented a plain surface, with the dentinal tubules being closed by the smear layer.
Keywords: Apicoectomy; Laser in dentistry; Smear layer